Pengaruh Volume Penjualan, Biaya Produksi, Dan Pajak Penghasilan Terhadap Laba Bersih Di Bursa Efek Indonesia - Eko Purwanto (LPPM ISNJ Bengkalis, 2021)
Sales volume refers to the income from the company's top operating results, and production costs are all costs related to the production carried out by the company, while income tax is the company's obligation to the state, which is binding. The purpose of the study was to examine the effect of sales volume, production costs, and income tax on the company's net income. This research uses the causality method with quantitative data and purposive sampling technique. The research population is all companies in the food and beverage industry sector on the Indonesia Stock Exchange from 2014 to 2020. The sample of this research is 12 companies with 84 financial statements. Data analysis used a regression model. The results of the study indicate that income tax affects the company's net profit. Meanwhile, sales volume and production costs do not affect the company's net profit. This research can be a reference for investors in choosing companies in the food and beverage sector.